PENGARUH LIKUIDITAS DAN RASIO AKTIVITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR KERAMIK, PORSELEN, DAN KACA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Riski, Kiki Mailan; Lie, Darwin; Jubi, Jubi; Ervina, Nelly (SULTANIST: Jurnal Manajemen dan Keuangan, 2018)
The purpose of this research is to know the description of liquidity, activity ratio and profitability also the influence of liquidity and activity ratio on the profitability at Firm in Sub Sector Keramik, Porselen, and Kaca listed in Indonesia Stock Exchange The research design in this research is a library research. The analysis data technique in this research are assumption classic test, qualitative and quantitative descriptive analysis.The result is Å¶ = -0,282 + 0,025X1 + 0,341X2. Correlation coefficient of r = 0,895 and R Square= 0,801. Simultaneous test results obtain Fcount > Ftable (44,343 < 3,44) or significant level obtained 0,00 < 0,05, means liquidity and activity ratio have significant effect on the profitability at Sub Sector Keramik, Porselen, and Kaca listed in Indonesia Stock Exchange. The t-test results for liquidity has tcount>ttable (4,377 > 2,07387) or significance level 0,00 < 0,05, means liquidity has significant effect on the profitability and for activity ratio shown tcount> ttable (9,409 > 2,07387) or significance level 0,00 < 0,05, means activity ratio has significant effect on the profitability at Sub Sector Keramik, Porselen, and Kaca listed in Indonesia Stock Exchange.The result of this research suggests company should continuously optimize used of debt and assets management companies to effectively and efficiently capable of producing and increase in the companyâ€™s performance which increased the rate of return received by investors.Â Keywords: Liquidity, Activity Ratio, and Profitability.